GIMAP5 maintains liver endothelial cell homeostasis and prevents portal hypertension. - Drzewiecki, Kaela; Choi, Jungmin; Brancale, Joseph; Leney-Greene, Michael A; Sari, Sinan; Dalgiç, Buket; Ünlüsoy Aksu, Aysel; Evirgen Şahin, Gülseren; Ozen, Ahmet; Baris, Safa; Karakoc-Aydiner, Elif; Jain, Dhanpat; et al. (J Exp Med, 2021)
Portal hypertension is a major contributor to decompensation and death from liver disease, a global health problem. Here, we demonstrate homozygous damaging mutations in GIMAP5, a small organellar GTPase, in four families with unexplained portal hypertension. We show that GIMAP5 is expressed in hepatic endothelial cells and that its loss in both humans and mice results in capillarization of liver sinusoidal endothelial cells (LSECs); this effect is also seen when GIMAP5 is selectively deleted in endothelial cells. Single-cell RNA-sequencing analysis in a GIMAP5-deficient mouse model reveals replacement of LSECs with capillarized endothelial cells, a reduction of macrovascular hepatic endothelial cells, and places GIMAP5 upstream of GATA4, a transcription factor required for LSEC specification. Thus, GIMAP5 is a critical regulator of liver endothelial cell homeostasis and, when absent, produces portal hypertension. These findings provide new insight into the pathogenesis of portal hypertension, a major contributor to morbidity and mortality from liver disease.

ACOX2 deficiency: A disorder of bile acid synthesis with transaminase elevation, liver fibrosis, ataxia, and cognitive impairment. - Vilarinho, Sílvia; Sari, Sinan; Mazzacuva, Francesca; Bilguvar, Kaya; Esendagli-Yilmaz, Güldal; Jain, Dhanpat; Akyol, Gülen; Dalgiç, Buket; Günel, Murat; Clayton, Peter T; Lifton, Richard P (Proc Natl Acad Sci U S A, 2016)
Acyl CoA Oxidase 2 (ACOX2) encodes branched-chain acyl-CoA oxidase, a peroxisomal enzyme believed to be involved in the metabolism of branched-chain fatty acids and bile acid intermediates. Deficiency of this enzyme has not been described previously. We report an 8-y-old male with intermittently elevated transaminase levels, liver fibrosis, mild ataxia, and cognitive impairment. Exome sequencing revealed a previously unidentified homozygous premature termination mutation (p.Y69*) in ACOX2 Immunohistochemistry confirmed the absence of ACOX2 expression in the patient's liver, and biochemical analysis showed marked elevation of intermediate bile acids upstream of ACOX2. These findings define a potentially treatable inborn error of bile acid biosynthesis caused by ACOX2 deficiency.
Keywords: Ataxia; Bile Acids and Salts; Child; Cognitive Dysfunction; Homozygote; Humans; Infant; Infant, Newborn; Liver; Liver Cirrhosis; Loss of Function Mutation; Male; Mutation; Oxidation-Reduction; Oxidoreductases; Transaminases

Recurrent recessive mutation in deoxyguanosine kinase causes idiopathic noncirrhotic portal hypertension. - Vilarinho, Sílvia; Sari, Sinan; Yilmaz, Güldal; Stiegler, Amy L; Boggon, Titus J; Jain, Dhanpat; Akyol, Gülen; Dalgiç, Buket; Günel, Murat; Lifton, Richard P (Hepatology, 2016)
UNLABELLED: Despite advances in the diagnosis and management of idiopathic noncirrhotic portal hypertension, its pathogenesis remains elusive. Insight may be gained from study of early-onset familial idiopathic noncirrhotic portal hypertension, in which Mendelian mutations may account for disease. We performed exome sequencing of eight subjects from six kindreds with onset of portal hypertension of indeterminate etiology during infancy or childhood. Three subjects from two consanguineous families shared the identical rare homozygous p.N46S mutation in DGUOK, a deoxyguanosine kinase required for mitochondrial DNA replication; haplotype sharing demonstrated that the mutation in the two families was inherited from a remote common ancestor. All three affected subjects had stable portal hypertension with noncirrhotic liver disease for 6-16 years of follow-up. This mutation impairs adenosine triphosphate binding and reduces catalytic activity. Loss-of-function mutations in DGUOK have previously been implicated in cirrhosis and liver failure but not in isolated portal hypertension. Interestingly, treatment of patients with human immunodeficiency viral infection with the nucleoside analogue didanosine is known to cause portal hypertension in a subset of patients and lowers deoxyguanosine kinase levels in vitro; the current findings implicate these effects on deoxyguanosine kinase in the causal mechanism. CONCLUSION: Our findings provide new insight into the mechanisms mediating inherited and acquired noncirrhotic portal hypertension, expand the phenotypic spectrum of DGUOK deficiency, and provide a new genetic test for a specific cause of idiopathic noncirrhotic portal hypertension. (Hepatology 2016;63:1977-1986).
Keywords: Adolescent; Amino Acid Sequence; Animals; Cattle; Child; Child, Preschool; DNA Mutational Analysis; Dogs; Female; Genes, Recessive; Homozygote; Humans; Hypertension, Portal; Infant; Liver Failure; Male; Molecular Sequence Data; Pedigree; Phosphotransferases (Alcohol Group Acceptor); Principal Component Analysis; Rats; Young Adult